First record of organochlorine pesticides in blood of wild and captive African leopards, Panthera pardus pardus (Linnaeus, 1758) - van As, Michelle; Smit, Nico J.; Wolmarans, Nico J.; Wepener, Victor (Frontiers in Environmental Science, 2022)
Compared to aquatic ecosystems, limited information exists on organochlorine accumulation in terrestrial ecosystems, and this is specifically true for terrestrial carnivores that have received limited attention in terms of studies on pollutant bioaccumulation. The African Leopard, Panthera pardus pardus (Linnaeus, 1758), is a popular focal species for research by ethologists and ecologists, but a noticeable knowledge gap exists with regards to toxicological aspects. To address this gap, the aim of this study was to determine baseline organochlorine pesticide (OCP) concentrations in blood of live wild and captive leopards in South Africa, and to explore the relationship between OCP levels and different conservation management strategies. Peripheral blood samples of seven captive and seven wild leopards, representing regular and melanistic individuals within the captive population, were collected while under sedation. The ΣOCP concentrations in blood serum were detected by means of GC-ECD. Statistical relationships among pesticide content in leopards from three geographical areas, different sexes, age groups and conservation status were examined. Captive leopards from this study had a slightly higher mean ΣOCP concentration (901 pg/ml) than wild leopards (768 pg/ml), and captive females had lower mean levels of ΣOCPs (797 pg/ml) than males (1,058 pg/ml). OCPs accumulated in the following order DDTs (27%) > HCHs (21%) > Heptachlors (15%) > CHLs (15%) > Drins (14%) > HCB (8%). Differences in OCP composition profiles of resampled captive individuals were also found. The sources of OCPs in the leopards can be attributed to the historic and current use of, e.g., DDT and HCHs, for malaria vector control and in insecticides/avicides in South Africa. For the captive leopards in this study the main source is possibly contaminated chicken that formed the major portion of their diet. This is the first report on OCP concentrations from leopards in Africa and highlights the need for this parameter to be considered in terms of the conservation management of healthy populations.